An international terminology for endometriosis, 2021,. Issue 4 (22nd October 2021) - ,; Tomassetti, Carla; Johnson, Neil P; Petrozza, John; Abrao, Mauricio S; Einarsson, Jon I; Horne, Andrew W; Lee, Ted T M; Missmer, Stacey; Vermeulen, Nathalie; Zondervan, Krina T; Grimbizis, Grigoris; et al.
Abstract: STUDY QUESTION: Can a set of terms and definitions be prepared on endometriosis that would be the basis for standardization in disease description, classification and research? SUMMARY ANSWER: The current paper outlines a list of 49 terms and definitions in the field of endometriosis. WHAT IS KNOWN ALREADY: Different classification systems have been developed for endometriosis, using different definitions for the disease, the different subtypes, symptoms and treatments. In addition, an International Glossary on Infertility and Fertility Care was published in 2017 by the International Committee for Monitoring Assisted Reproductive Technologies (ICMART) in collaboration with other organisations. STUDY DESIGN, SIZE, DURATION: An international working group convened over the development of a classification or descriptive system for endometriosis. As a basis for such a system, a terminology for endometriosis was considered a condition sine qua non. The working group listed a number of terms relevant to be included in the terminology, documented currently used and published definitions, and discussed and adapted them until consensus was reached within the working group. Following stakeholder review, further terms were added, and definitions further clarified. PARTICIPANTS/MATERIALS, SETTING, METHODS: Although definitions were collected through published literature, the final set of terms and definitions is to be considered consensus-based. After finalization of the first draft, the members of the international societies and other stakeholders were consulted for feedback and comments, which led to further adaptations. MAIN RESULTS AND THE ROLE OF CHANCE: A list of 49 terms and definitions in the field of endometriosis is presented, including a definition for endometriosis and its subtypes, different locations, interventions, symptoms and outcomes. Endometriosis is defined as a disease characterized by the presence of endometrium-like epithelium and/or stroma outside the endometrium and myometrium, usually with an associated inflammatory process. LIMITATIONS, REASONS FOR CAUTION: Future research may require further refinement of the presented definitions. WIDER IMPLICATIONS OF THE FINDINGS: The application of the defined terms aims to facilitate harmonization in endometriosis research and clinical practice. STUDY FUNDING/COMPETING INTEREST(S): The meetings and activities of the working group were funded by the American Association of Gynecologic Laparoscopists, European Society for Gynecological Endoscopy, European Society of Human Reproduction and Embryology and World Endometriosis Society. A.W.H. reports grant funding from the MRC, NIHR, CSO, Wellbeing of Women, Roche Diagnostics, Astra Zeneca, Ferring, Charles Wolfson Charitable Trust, Standard Life, Consultancy fees from Roche Diagnostics, AbbVie, Nordic Pharma and Ferring, outside the submitted work. In addition, A.W.H. has a patent Serum biomarker for endometriosis pending. N.P.J. reports personal fees from Abbott, Guerbet, Myovant Sciences, Vifor Pharma, Roche Diagnostics outside the submitted work; he is also President of the World Endometriosis Society and chair of the trust board. S.M. reports grants and personal fees from AbbVie, and personal fees from Roche outside the submitted work. C.T. reports grants, non-financial support and other from Merck SA, non-financial support and other from Gedeon Richter, non-financial support from Ferring Pharmaceuticals, outside the submitted work and without private revenue. K.T.Z. reports grants from Bayer Healthcare, MDNA Life Sciences, Roche Diagnostics Inc, Volition Rx, outside the submitted work; she is also a Board member (Secretary) of the World Endometriosis Society and World Endometriosis Research Foundation, Research Advisory Board member of Wellbeing of Women, UK (research charity), and Chair, Research Directions Working Group, World Endometriosis Society. J.P reports personal fees from Hologic, Inc., outside the submitted work; he is also a member of the executive boards of ASRM and SRS. The other authors had nothing to disclose. TRIAL REGISTRATION NUMBER: N/A.